Transient Electro-Thermal Analysis of a Common Source Amplifier Circuit with a Physics-based MOSFET Model - Tao Pan; Dazhi Ding; Hanxiang Li; Xiaolin Cheng (Applied Computational Electromagnetics Society Journal (ACES), 2019)
An algorithm that combines a common source amplifier with the physics-based metal-oxidesemiconductor field effect transistor (MOSFET) model is proposed. By solving the coupled drift-diffusion model equations with spectral element time-domain (SETD) method, the distribution of electron quasi-Fermi potential, hole quasi-Fermi potential and the potential inside the MOSFET is obtained. The corresponding current densities and electric intensities distributed in the device can be used to couple the heat conduction equation. Furthermore, the Kirchhoff laws should be satisfied when the MOSFET device is inserted in the circuit. The Newton-Raphson method is used to solve the nonlinear circuit equations due to the existence of semiconductor devices. The transient electro-thermal characteristics of a common source amplifier circuit have been analyzed, and the numerical results demonstrate the validity of the proposed method.